Développement durable et agriculture durable : sens du concept de « durabilité » à travers la presse régionale et le discours des agriculteurs - Lise Bihannic; Élisabeth Michel-Guillou (Développement Durable et Territoires)
This study focuses on the meaning of the concepts of sustainable development and sustainable agriculture. First, this study deals with a content analysis of their circulation in the regional papers (specialized in agriculture and popular newspaper). Second, it is interested in the appropriation of theses concepts farmers. Semi-structured interviews were carried out with these stakeholders concerned with these issues. The aim of the study is to compare these two content analyses and to highlight the social representations of these concepts. We postulate that these representations are a form of knowledge which is socially constructed. They are a guide to action and that they take shape, they are transmitted and they evolve in the heart of communication (Moscovici, 1976).